Parental Emotion Socialization and Child Adjustment in Greek Families: Supportive vs. Non-Supportive Parenting - Maria Markoulaki; Christina Dimitrakaki; Andoniki Naska; Katerina Papanikolaou; Georgios Giannakopoulos (Children, 2025)
Background/Objectives: Parental emotion socialization is a key influence on children’s emotional regulation and psychosocial development. This study examined how supportive and non-supportive parental responses to children’s negative emotions are associated with internalizing and externalizing problems and social competence among Greek children aged 6–12 years. Methods: A non-experimental, cross-sectional correlational study using convenience sampling was conducted with 100 Greek parents who completed the Coping with Children’s Negative Emotions Scale and the Child Behavior Checklist. Correlation and multiple regression analyses were used to examine associations between parenting responses and child outcomes, controlling for child age, child gender, and parent gender. Results: Minimization/devaluation responses were significantly associated with higher internalizing problems (β = 0.396, p = 0.009), externalizing problems (β = 0.264, p = 0.048), and total problems (β = 0.320, p = 0.012). Punitive responses significantly predicted externalizing (β = 0.383, p = 0.003) and total problems (β = 0.304, p = 0.004). Supportive strategies (e.g., emotion-focused and problem-focused responses) did not significantly predict lower problem scores but were positively correlated with social competence (e.g., problem-focused response: ρ = 0.25, p = 0.017). Parent gender predicted minimization/devaluation responses, with mothers scoring higher than fathers (β = 0.308, p = 0.006). Conclusions: Non-supportive parental responses—especially punitive and dismissive behaviors—are robustly associated with increased behavioral and emotional difficulties in children. While supportive strategies may contribute to social competence, their benefits appear diminished in the presence of negative parenting practices. These findings highlight the importance of culturally sensitive interventions tailored to Greek family dynamics. Despite limitations such as the use of self-report measures and a non-representative sample, this study contributes valuable insights into emotion socialization and child adjustment in a specific cultural context.